KESEPADANAN ANDUNG – ANDUNG BATAK TOBA - Roswita Silalahi; Parlindungan Purba (Fakultas Sastra Universitas Negeri Malang, 2015)
Andung-Andung (AA) ‘lamentation’ refers to sad feelings caused by the death of the beloved one in Toba Batak community. Lamentation consists of poetic expression and dominantly is recited by sad wives in expressing their deepest anguish, which makes the lamentation not easy to translate due to its specific features. The study was conducted to document and translate AA into Indonesian by using descriptive-qualitative method. The data were gathered through observation, recording, interviewing, analyzing contents and having a FGD. The data were analyzed by applying interactive analysis technique involving the theory of linguistic anthropology to interpret the meaning , content analysis, combined with meaning-based translation process to reach idiomatic translation.